143k views
3 votes
For which quadratic function is -3 the constant term?

a. y= (3x + 1)(-x-3)
b. x^2-3x+3
c. f(x)= (x-3)(x-3)
d. y= -3x^2+3x+9​

User Sense
by
6.1k points

1 Answer

3 votes

Answer:

A

Explanation:

For b, the constant term is 3, not -3. B is incorrect.

For c, when the brackets are removed using foil, -3 * - 3 = 9. C is incorrect.

For d, There is no reduction, alteration or math procedure that you can use that will make the constant term anything but 9. The answer is not D.

======================

That means you are left with A which must be right or the question isn't. Turns our that A is the answer -3 * 1 = - 3

User DarrylG
by
6.1k points